FAKTOR KEMENANGAN DARMAWAN, SH. PADA PILKADES DESA KUALU KECAMATAN TAMBANG KABUPATEN KAMPAR TAHUN 2021-2027 - Widianingsih '; Adlin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
his study aims to look at Darmawan, SH's winning factors in the Pilkades of Desa Kualu. This study uses candidate performance theory in voting behavior where there are 4 factors, namely candidate quality, candidate nature, candidate popularity, and sociological factors. This study used a descriptive approach with a qualitative type, then the data collection techniques used were interviews, observation and documentation, while the data analysis techniques were carried out by collecting information through interviews. The results of this study indicate that Darmawan, SH's victory in the village head election consisted of 3 main factors, namely popularity, a factor that influenced voters in determining their choices, where Darmawan S.H's fame in the village of Kualu from the other four candidate candidates led to the large number of votes cast. obtain Darmawan S.H in the village head election, then the next factor is the candidate's image factor, where the candidate's image is very closely related to the popularity of the candidate, where Darmawan S.H's fame is due to his good image in the eyes of the community, the next factor, namely, sociological factors, in Kualu village itself is still holding tight to ethnicity and custom, where in the last village head election, the role of each tribe from the candidate candidates was inseparable, where Darmawan S.H, who is of Malay ethnicity, received full support from the Malay tribe, Malay tribes in the village of Kualu united and worked hand in hand to help Darmawan S.H in the village head election in the village of Kualu. Keywords: Winning Factor, Behavior, Village Head